Circulating free DNA as a marker of response to chemoradiation in locally advanced head and neck squamous cell carcinoma - Tripti Verma; Swati Kumari; Sridhar Mishra; Madhup Rastogi; Vandana Tiwari; Gaurav R Agarwal; Nidhi Anand; Nuzhat Husain (Wolters Kluwer Medknow Publications, 2020)
Context: Liquid biopsy has moved from bench to bedside as a non-invasive biomarker for early diagnosis and monitoring treatment response. Objective: This study investigated the role of circulating free DNA (cfDNA) as a diagnostic marker in locally advanced head and neck squamous cell carcinoma (HNSCC) and in monitoring response to chemoradiation therapy. Materials and Methods: Serum was collected from treatment naïve, histopathologically diagnosed tumors in 24 HNSCC cases and 16 normal controls. CfDNA levels were quantified using β globin gene amplification. Results: The cfDNA level was significantly elevated in HNSCC (992.67 ± 657.43 ng/mL) as compared to healthy controls (60.65 ± 30.42 ng/mL, P = <0.001). The levels of cfDNA did not significantly correlate with TNM stage, lymph node involvement and grade. In responders, percentage decrease in cfDNA levels was 9.57% and 29.66%, whereas in nonresponders percentage increase was 13.28% and 24.52% at the end of three months of follow-up. Conclusion: Our study adds to the evidence that cfDNA levels are significantly higher in HNSCC cases and provides some evidence that levels increase with tumor progression. CfDNA may be a promising prospective non-invasive marker to predict response in patients undergoing chemo-radiotherapy.